2022
DOI: 10.1159/000520657
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Relationships in Inheritable Idiopathic Pulmonary Fibrosis: A Greek National Cohort Study

Abstract: <b><i>Background:</i></b> Monogenic and polygenic inheritances are evidenced for idiopathic pulmonary fibrosis (IPF). Pathogenic variations in surfactant protein-related genes, telomere-related genes (TRGs), and a single-nucleotide polymorphism in the promoter of <i>MUC5B</i> gene encoding mucin 5B (rs35705950 T risk allele) are reported. This French-Greek collaborative study, Gen-Phen-Re-GreekS in inheritable IPF (iIPF), aimed to investigate genetic components and patients’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Elaborate genealogical research studies have shown that a latency period of >300 years may pass before the cumulative effect of telomere shortening eventually leads to familial PF in TRG mutation carriers [ 141 , 155 ]. In addition to personal/familial extra-pulmonary abnormalities suggestive of STS involving the skin, the liver, and the bone marrow, the disease is uniformly progressive, irrespective of its phenotypic heterogeneity, and bears a reduced transplant-free survival time [ 18 , 19 , 32 , 156 , 157 ]. The increased risk for complications and high mortality post-lung-transplantation is due mostly to sepsis, greater than expected bone-marrow suppression and increased rates of chronic allograft dysfunction and airway complications (dehiscence and stenosis) [ 156 , 157 , 158 , 159 , 160 ].…”
Section: Clinical Implications Of Carriership Of Pathogenic Variation...mentioning
confidence: 99%
See 2 more Smart Citations
“…Elaborate genealogical research studies have shown that a latency period of >300 years may pass before the cumulative effect of telomere shortening eventually leads to familial PF in TRG mutation carriers [ 141 , 155 ]. In addition to personal/familial extra-pulmonary abnormalities suggestive of STS involving the skin, the liver, and the bone marrow, the disease is uniformly progressive, irrespective of its phenotypic heterogeneity, and bears a reduced transplant-free survival time [ 18 , 19 , 32 , 156 , 157 ]. The increased risk for complications and high mortality post-lung-transplantation is due mostly to sepsis, greater than expected bone-marrow suppression and increased rates of chronic allograft dysfunction and airway complications (dehiscence and stenosis) [ 156 , 157 , 158 , 159 , 160 ].…”
Section: Clinical Implications Of Carriership Of Pathogenic Variation...mentioning
confidence: 99%
“…Therefore, telomeropathy is now recognized in addition to age, frailty, pulmonary hypertension, cardiovascular risk, and lung cancer as a parameter for which careful consideration must be given to pre-operative optimization, surgical technique, pulmonary rehabilitation, and a tailored immunosuppressive treatment protocol to produce the best post-transplantation outcomes [ 127 , 143 , 162 , 163 , 164 , 165 , 166 ]. Bone-marrow failure presenting as myelodysplastic syndrome (MDS) or acute myeloid leukemia (AML) may arise at any timepoint in the disease’s course in almost 10% of patients, especially those younger than 65 years old [ 18 , 19 , 32 , 141 , 167 , 168 , 169 , 170 ]. Naturally occurring somatic mutations in telomere maintenance genes observed in some patients with familial-PF potentially might rescue premature age-related clonal hematopoiesis and transformation to MDS/AML [ 139 , 171 ].…”
Section: Clinical Implications Of Carriership Of Pathogenic Variation...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has suggested that the S100 calcium-binding protein A12 (S100A12) could potentially serve as a prognostic serum biomarker in IPF [ 10 ]. Furthermore, according to studies, genomic approaches may include the identification of microRNAs and the polymorphism in the promoter region of MUC5B, as well as some other rare mutations [ 11 , 12 ]. Regarding novel approaches, recently, the serum proteomic profile has the potential to offer valuable insights into the heterogeneity of IPF and to uncover protein alterations that can aid in its diagnosis and treatment decisions [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has examined genetic associations, common single nucleotide polymorphisms (SNP) and rare gene mutations are associated with their development 25 . Rare mutations in genes telomerase reverse transcriptase ( TERT ) 27 , telomerase RNA component ( TERC ) 28 , dyskeratosis congenita 1 ( DKC1 ) 29 , telomere repeat binding factor 1-interacting nuclear factor 2 ( TINF2 ) 30 , regulator of telomere length 1 ( RTEL1 ), zinc finger CCHC-type containing 8 ( ZCCHC8 ), poly(A)-specific ribonuclease ( PARN ) 31 , surfactant protein C ( SFTPC ) 32 , surfactant protein A2 ( SFTPA2 ) 33 , the ATP-binding cassette-type family A member 3 transporter ( ABCA3 ) 34 ), and common variants of 10 loci (3q26, 4q22, 5p15, 6p24, 7q22, 10q24, 11p15, 13q34, 15q14-15, and 19p13) 25 are associated with f-IPF.…”
Section: Introductionmentioning
confidence: 99%